Evaluasi Program Permainan Tradisional (Cublak-Cublak Suweng) Menggunakan Model Alkin - Atika Lindarti; Ryan Hasanudin (UIN Raden Mas Said Surakarta, 2021)
The problem in this research is that the learning program using the traditional cublak-cublak suweng game has never been evaluated. The research aims to evaluate the program using the Alkin Model. This research uses a mixed method, which is a combination of qualitative and quantitative research using a descriptive approach. The research was conducted at TKIT Az Zahra, Sukodono, Sragen in January-March 2020. The subjects in the study were B1 class children and teachers, the research informant was the principal. Methods of data collection using observation, interviews and documentation. The data validity technique used source triangulation and method triangulation. The qualitative data analysis technique used an interactive analysis model, while the quantitative questionnaire was analyzed using the percentage (percentile) analysis formula. The conclusion of the study is the evaluation of the input stage in the form of students, infrastructure and teachers in good categories. Evaluation of the process stage in the form of preparation before starting the activity to completing the activity in good category. The evaluation of the output stage in this study is categorized as good with a daily assessment that continues to increase with reference to indicators from STTPA.